ANALISIS KEMAMPUAN PENDAPATAN ASLI DAERAH DALAM MEMBIAYAI BELANJA DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN KUPAN - Imelda R. Nayuf; Agnes K. B. Mudamakin; Fransiskus N. Naiola; Christian Timotius Peilouw (JAKA - Jurnal Jurusan Akuntasi, 2021)
This study aims to determine how much the ability of local revenue in financing the regional expenditure of Kupang Regency. This research has the benefit of increasing knowledge about how big the level of Local Original Income of the Kupang Regency Government is.The research method used in this research is quantitative The data analysis technique used in this study is by using the formula for the degree of fiscal decentralization, the ratio of regional financial independence, analysis of the regional financial dependence ratio, the effectiveness ratio of the pad, and the regional financial efficiency ratio. The results obtained from this study are the financial capacity management of Kupang Regency measured from the level of regional autonomy included in the very poor criteria and the level of regional financial independence ratio was very low. The effectiveness ratio is less effective with an average of 80%, the efficiency ratio level is an average of 99.98%, where in 2017 the percentage is 106.92%, in 2018 the percentage is 98.77%, in 2019 the percentage is 96, 55%, in 2020 the percentage is 97.76% and the spending growth ratio is 6.48% on average. Where in 2017 the percentage was 14.95%, in 2018 the percentage was 1.03%, in 2019 the percentage was 4.24%, in 2020 the percentage was 5.70%.